2008
DOI: 10.1021/es070485s
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Nanoparticles of Organic Carbon and Soot in Flames and Vehicle Exhausts

Abstract: We measured the size distribution and UV extinction spectra of carbonaceous nanoparticles present in the size range of 1-100 nm in the exhausts of 2004 model gasoline and diesel powered vehicles and compared the results with those obtained in premixed flames. In addition to soot particles, nanoparticles of organic carbon (NOC) were measured in the emissions of these test vehicles in significant number and mass concentrations. The number and mass concentration of NOC was higher than soot in gasoline vehicle emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 18 publications
6
51
2
Order By: Relevance
“…It is suggested that they are carbonaceous particles formed during combustion. 20,21 Negative health effects of particle emissions [22][23][24][25] have driven stricter emission standards for diesel particulate emissions. More stringent traffic emission limits drive engine and vehicle manufacturers to utilize new technologies to reduce emissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that they are carbonaceous particles formed during combustion. 20,21 Negative health effects of particle emissions [22][23][24][25] have driven stricter emission standards for diesel particulate emissions. More stringent traffic emission limits drive engine and vehicle manufacturers to utilize new technologies to reduce emissions.…”
Section: Discussionmentioning
confidence: 99%
“…The origin or composition of these nonvolatile particles in unknown, but it has been suggested that they are heavy HCs formed during combustion. 20,21 Effect of DOC ؉ POC on Particles When the engine was equipped with the DOC ϩ POC combination, no nucleation-mode particles were detected at any of the four load points. This is shown in Figure 3, where the size distributions measured with and without the thermodenuder are shown.…”
Section: Particle Size Distributionsmentioning
confidence: 99%
“…Owing to their small size and complicated chemical and physical characteristics (3)(4)(5)(6), atmospheric particles resulting from traffic emissions pose a significant risk to human health (7)(8)(9)(10)(11)(12), and also contribute to anthropogenic forcing of climate (13,14). Previous research on vehicular emissions has demonstrated the presence of soot and ash (3,15) and solid sub-10-nm core particles (4)(5)(6) in primary emissions from vehicles and engines and their variation, depending on vehicle technologies (4,6), the properties of fuels and lubricant oils (15,16), and driving conditions (15)(16)(17). In addition to particles, exhaust typically contains species that reside in the gaseous phase in the undiluted high-temperature exhaust (5,18,19) but condense or even nucleate to the particle phase immediately after the exhaust is released to the atmosphere.…”
mentioning
confidence: 99%
“…Some studies have also shown that nanosized clusters have a role in engine emission formation (4,25). Research on particle number concentrations near traffic has shown highly elevated concentrations (of the order of 10 5 -10 6 ) of ultrafine particles near roadways (2,26), also indicating the likelihood of high concentrations of nanosized particles and clusters existing in such environments.…”
mentioning
confidence: 99%
“…Thermal and diffusion charging mechanisms are explored to explain the measured charge distributions, and we discuss the implications of the results for particle coagulation at high temperature. The particles are produced in atmospheric pressure premixed flames, which have been previously examined with many complementary particle diagnostics with sensitivity to particles/macromolecules as small as 1 nm, including multiwavelength optical, microscopy and mobility measurements (D'Alessio et al 2005Minutolo et al 1999;Sgro et al 2008). While the various measurement techniques are in excellent agreement in flame conditions that eventually produce particles larger than 3-5 nm, the DMA measurements are significantly lower than in situ optical measurements in flame conditions where the size distribution is unimodal with a modal diameter, d modal ∼ 2 nm ).…”
Section: Introductionmentioning
confidence: 99%